Modern Motivational Discourses: from «Correspondence» Metaphor to «Becoming» Metaphor - Klymchuk, Vitalii (Psychological Prospects Journal, 2014)
Modern psychology of motivation is faced with new challenges, in particular – growing dominance of postnonclassical scientific paradigm within which to replace the classical «object-subject» and non-classical «subject-subject» dyad comes «subject-subject-context» triad. Thus psychology of motivation, first, lyfaces the need to be social psychology of motivation, secondly, the dynamic changes of a human in the modern world, and thirdly, does not lose its scientific and practicality. The conclusions about dominant position of four discourses in field of psychology of motivation (authenticity discourse, evaluation discourse, expansion discourse and construction discourse) are made on the basis of modern scientific texts reviews. The analysis of these three discourses leads us to understanding of theirs transitional status (from metaphor «correspondence» (authenticity, evaluation and expansion discourses) to metaphor «becoming» (construction discourse)). It is concluded that within the discourse of construction psychology motivation respond to all the challenges of postmodernism and integrates with modern postnonclassical scientific paradigm.
Keywords: authenticity, metaphor «correspondence», metaphor «becoming», motivational discourse, self-actualization, self-determination.